Costa Rica: la fabricación de Juan Rafael Mora (siglos xix-xxi) - Víctor Hugo Acuña Ortega (Caravelle)
This paper studies Juan Rafael Mora’s making to turn him into a hero of the Costarican nation, because of his participation in the war against the North American filibuster William Walker (1856-1857). It shows that Mora himself started this process and analizes the memorial circumstances during which the character’s heroic attributes were forged, from 1850 till today. In each circumstance, its instigators, protagonists and the social and historical context are identified.